EFFECT OF MANAGEMENT INNOVATION, TRANSFORMATIONAL LEADERSHIP, AND KNOWLEDGE SHARING ON MARKET PERFORMANCE OF INDONESIAN CONSUMER GOODS COMPANY - Purwanto, Agus; Purba, John Tampil; Bernarto, Innocentius; Sijabat, Rosdiana (Universitas Brawijaya, Indonesia, 2021)
Transformational leadership greatly influences the management innovation and market performance of consumer good companies enterprises. According to the survey data about 244 employees of consumer goods companies, an empirical study was conducted on the relationship between transformational leadership, management innovation, knowledge sharing, market performance of consumer good companies enterprises, and analysis was made on the mediating effect of management innovation and knowledge sharing. The results showed that knowledge sharing has no significant effect on the market performance of consumer goods companies. Management innovation has not a significant effect on the market performance of consumer goods companies. Transformational leadership has no significant effect on the knowledge sharing of consumer goods companies. Transformational leadership has a significant effect on management innovation of consumer goods. Transformational leadership has no significant positive effect on the market performance of consumer goods companies.